Phacomatosis cesioflammea with cutis marmorata-like lesions and unusual extracutaneous abnormalities: Is it a distinct disorder? - Shyam B Verma; Hitesh K Desai; Vishal N Shah; Rudolf Happle (Wolters Kluwer Medknow Publications, 2017)
A 2-month-old boy was presented with widespread lateralized blue macules (nevus cesius), an extensive nevus flammeus, and large patches of cutis marmorata telangiectatica congenita. Moreover, he had macrocephaly, a coarse facial appearance with depressed nasal bridge, retinal abnormalities, septal defects of the heart, and obliteration of the left brachiocephalic vein and major veins of the left arm with pronounced collateralization. The multisystem disorder of this boy cannot be categorized within the present classification of distinct types of phacomatosis pigmentovascularis. Although some similar complex cases have previously been reported, it seems too early to give them a specific name. Rather, the present case should be included, so far, into the group of unclassifiable types of phacomatosis pigmentovascularis.